Practical Mono - Mamone, Mark (Apress, 2012)
Ever since the .NET initiative launched in January 2000 and the Visual Studio .NET beta subsequently launched in October 2000, the .NET train has been gaining speed; it now is the number-one development platform for the Windows operating system. However, you may have noticed a key point in that statement: for the Windows operating system! Yes, you guessed it: Microsoft targeted the .NET technology suite at the Windows operating system only; therefore, at the time of its launch, .NET was not available on other platforms such as Unix, Mac OS X, or Linux. This is not surprising, as Microsoft develops the Windows operating system and doesn’t want to invest time in creating versions for competing operating systems; however, in the corporate world, other operating systems exist and for good reasons.¨